Cortázar, Calvino, Antonioni, Maselli: Writing-Photography and cinema in its Model Kits (El Hilo de la Fabula, 2025)
During the early years of the second half of the 20th century, Julio Cortázar was concerned with the ways of narrating and revealing the potentialities of interpretation and reception. Similarly, during this period, Italo Calvino attempted to move beyond the opacity imposed by neo-realism, by proposing a lighter and more meta-referential writing.Both authors used photography and intertextual games between word and image, form and nothingness, in order to reflect on these meta and intertextual complexities. Antonioni and Maselli interpreted these proposals intertextually.
Keywords: Cortázar; Calvino; Antonioni; Maselli; Writing; Photography; Cinema; Meta/intertextuality